Big data analytics for marketing in database-driven companies - Hadi, Harem; Yasin , Hajar Maseeh (International Journal of Scientific World, 2025)
Database-driven businesses are using Big Data Analytics (BDA) to increase marketing efficacy as a result ‎of the boom in data generation brought about by the spread of digital technologies. This study examines the ‎use of BDA by well-known companies, including Amazon, Netflix, Coca-Cola, Nike, and H&M, to ‎accomplish strategic marketing goals like real-time engagement, predictive targeting, and customization. ‎The study examines several data processing methods, from machine learning and neural networks to ‎sentiment analysis and recommendation systems, using a comparative case-based methodology. It also ‎emphasizes the different business implications that are realized across sectors. In addition to being in line ‎with earlier theoretical frameworks, the research connects them to useful, real-world applications. Results ‎show that BDA dramatically increases ROI, conversion rates, and customer retention; yet, it also comes ‎with drawbacks including algorithmic bias, data privacy, and dynamic market adaptation. Finally, by offering ‎a thorough examination of BDA in marketing and highlighting the strategic significance of integrated, ‎moral, and technologically sophisticated data practices for long-term competitive advantage, this study ‎adds to the body of knowledge‎.